Contemporary outcomes of patients undergoing robotic-assisted radical cystectomy: A comparative analysis between intracorporeal ileal conduit and neobladder urinary diversions - Jordan M. Rich; Shivaram Cumarasamy; Daniel Ranti; Etienne Lavallee; Kyrollis Attalla; John P. Sfakianos; Nikhil Waingankar; Peter N. Wiklund; Reza Mehrazin (Asian Journal of Urology, 2023)
Objective: We aimed to compare perioperative and oncologic outcomes for patients undergoing robotic-assisted radical cystectomy (RARC) with intracorporeal ileal conduit (IC) and neobladder (NB) urinary diversion. Methods: Patients undergoing RARC with intracorporeal urinary diversion between January 2017 and January 2022 at the Icahn School of Medicine at Mount Sinai, New York, NY, USA were indexed. Baseline demographics, clinical characteristics, perioperative, and oncologic outcomes were analyzed. Survival was estimated with Kaplan-Meier plots. Results: Of 261 patients (206 [78.9%] male), 190 (72.8%) received IC while 71 (27.2%) received NB diversion. Median age was greater in the IC group (71 [interquartile range, IQR 65–78] years vs. 64 [IQR 59–67] years, p<0.001) and BMI was 26.6 (IQR 23.2–30.4) kg/m2. IC group was more likely to have prior abdominal or pelvic radiation (15.8% vs. 2.8%, p=0.014). American Association of Anesthesiologists scores were comparable between groups. The IC group had a higher proportion of patients with pathological tumor stage 2 (pT2) tumors (34 [17.9%] vs. 10 [14.1%], p=0.008) and pathological node stages pN2–N3 (28 [14.7%] vs. 3 [4.2%], p<0.001). The IC group had less median operative time (272 [IQR 246–306] min vs. 341 [IQR 303–378] min, p<0.001) and estimated blood loss (250 [150–500] mL vs. 325 [200–575] mL, p=0.002). Thirty- and 90-day complication rates were 44.4% and 50.2%, respectively, and comparable between groups. Clavien-Dindo grades 3–5 complications occurred in 27 (10.3%) and 34 (13.0%) patients within 30 and 90 days, respectively, with comparable rates between groups. Median follow-up was 324 (IQR 167–552) days, and comparable between groups. Kaplan-Meier estimate for overall survival at 24 months was 89% for the IC cohort and 93% for the NB cohort (hazard ratio 1.23, 95% confidence interval 1.05–2.42, p=0.02). Kaplan-Meier estimate for recurrence-free survival at 24 months was 74% for IC and 87% for NB (hazard ratio 1.81, 95% confidence interval 0.82–4.04, p=0.10). Conclusion: Patients undergoing intracorporeal IC urinary diversion had higher postoperative cancer stage, increased nodal involvement, similar complications outcomes, decreased overall survival, and similar recurrence-free survival compared to patients undergoing RARC with intracorporeal NB urinary diversion.